A population based time series analysis of asthma hospitalisations in Ontario, Canada: 1988 to 2000 - Upshur Ross EG; Mamdani Muhammad M; Crighton Eric J (BMC, 2001)
Abstract Background Asthma is a common yet incompletely understood health problem associated with a high morbidity burden. A wide variety of seasonally variable environmental stimuli such as viruses and air pollution are believed to influence asthma morbidity. This study set out to examine the seasonal patterns of asthma hospitalisations in relation to age and gender for the province of Ontario over a period of 12 years. Methods A retrospective, population-based study design was used to assess temporal patterns in hospitalisations for asthma from April 1, 1988 to March 31, 2000. Approximately 14 million residents of Ontario eligible for universal healthcare coverage during this time were included for analysis. Time series analyses were conducted on monthly aggregations of hospitalisations. Results There is strong evidence of an autumn peak and summer trough seasonal pattern occurring every year over the 12-year period (Fisher-Kappa (FK) = 23.93, p > 0.01; Bartlett Kolmogorov Smirnov (BKS) = 0.459, p < 0.01). This pattern was observed in both sexes. However, young males (0-4 years) were hospitalised at two to three times the rate of females of the same age. Rates were much lower in the older age groups. A downward trend in asthma hospitalisations was observed in the total population over the twelve-year period (beta = -0.980, p < 0.01). Conclusions A clear and consistent seasonal pattern was observed in this study for asthma hospitalisations. These findings have important implications for the development of effective management and prevention strategies.